PERFORMANCE EVALUATION IN INSTITUTIONAL SPORTS PROGRAMS - Vitali, Rodrigo Oliveira (LUMEN ET VIRTUS, 2023)
The present study aimed to analyze the performance evaluation processes in institutional sports programs in Brazil, identifying the main indicators used, the challenges faced and the potentialities evidenced by national experiences. To this end, a qualitative research of exploratory and descriptive nature was carried out, based on the documentary review of technical reports, academic articles and institutional productions referring to initiatives such as the Sports and Leisure Program of the City, Second Half Program, Healthy Life Program, Agita São Paulo and local projects conducted by civil society organizations. The analysis of the data revealed that the absence of clear parameters and permanent monitoring mechanisms still constitutes a significant limitation that compromises the effectiveness and social legitimacy of these policies. It was observed that most programs predominantly use indicators of attendance and participation, neglecting dimensions such as pedagogical quality, financial sustainability, social impact and perception of beneficiaries. It was found that experiences that incorporate participatory strategies and invest in intersectoral integration have a greater capacity for consolidating results and collective appropriation of the learning generated. The findings highlight the importance of building evaluation methodologies that value cultural diversity, transparency, and ethical commitment, recognizing that evaluation should be understood as a formative and permanent process. The study concludes that the qualification of evaluation practices, the continuous training of teams and the strengthening of institutional partnerships represent strategic paths to consolidate more inclusive, effective and socially recognized sports policies.